Judicial independence under threat - Giannoulopoulos, Dimitrios; McDermott, Yvonne (Oxford : Published for the British Academy by Oxford University Press, 2022)
'Judicial Independence Under Threat' seeks to situate contemporary challenges to judicial independence in their proper legal, philosophical, political, and historical contexts. It asks how threats to judicial independence can be protected against.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Judicial independence; Separation of powers; Advice and Rights; Laws of specific jurisdictions & specific areas of law